2020
DOI: 10.1007/s10792-020-01592-1
|View full text |Cite
|
Sign up to set email alerts
|

Ocular involvement in coronavirus disease 2019 (COVID-19): a clinical and molecular analysis

Abstract: Purpose Coronavirus disease 2019 (COVID-19) caused a global pandemic with millions infected worldwide. Little is known on the ocular involvement associated with the disease. The aim of this study was to assess the clinical and molecular ocular involvement among patients with confirmed COVID-19 admitted to a tertiary care facility. Methods Consecutive patients admitted to the COVID-19 Ward of the Shamir Medical Center in Israel during March and April, 2020 were included. The control group included patients nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 20 publications
(27 reference statements)
2
27
0
2
Order By: Relevance
“…Most of the studies were official recommendations of ophthalmological societies for precaution and prevention of SARS-CoV-2 infection or studies on the impact of COVID-19 outbreak on eye care. Currently, the presence and prevalence of ocular manifestations in SARS-CoV-2 infection, consistent with conjunctivitis and including conjunctival hyperemia, chemosis, epiphora, or increased secretions, are still controversial (92)(93)(94)(95). Despite it was reported that only a small percentage (from about 1 to 6%) of SARS-CoV-2 positive patients developed signs of conjunctivitis, other studies showed that up to 31% of SARS-CoV-2 hospitalized patients presented conjunctivitis (96)(97)(98)(99).…”
Section: Eyesmentioning
confidence: 99%
“…Most of the studies were official recommendations of ophthalmological societies for precaution and prevention of SARS-CoV-2 infection or studies on the impact of COVID-19 outbreak on eye care. Currently, the presence and prevalence of ocular manifestations in SARS-CoV-2 infection, consistent with conjunctivitis and including conjunctival hyperemia, chemosis, epiphora, or increased secretions, are still controversial (92)(93)(94)(95). Despite it was reported that only a small percentage (from about 1 to 6%) of SARS-CoV-2 positive patients developed signs of conjunctivitis, other studies showed that up to 31% of SARS-CoV-2 hospitalized patients presented conjunctivitis (96)(97)(98)(99).…”
Section: Eyesmentioning
confidence: 99%
“…Another issue worth exploring is the inconsistent results of the ocular surface RT-PCR among different studies. Four studies conducted by Seah, Meduri, Pirraglia, and Shemer revealed zero positive rates [ 8 , 31 , 34 , 38 ]. However, 21 (55.3%) out of 38 COVID-19 patients in Hanege's study had positive RT-PCT results in conjunctival swabs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there is scant information on patients with severe form of the disease. Due to lack of possibility to perform ophthalmic examination on patients in serious condition staying in ICUs, they were excluded from most studies [ 35 ].…”
Section: Conjunctivitismentioning
confidence: 99%